Impact of Foreign Language Classroom Anxiety on Higher Education Students Academic Success: Mediating Role of Emotional Intelligence and Moderating Influence of Classroom Environment - Han, Siyuan; Li, Yiman; Haider, Syed Arslan (Frontiers in Psychology, 2022)
The current study aimed to investigate the impact of foreign language classroom anxiety (FLCA) on academic success through mediating role of emotional intelligence communication (EIC) and moderating role of class room environment. Due to the disruptive impacts of the COVID-19 pandemic, teaching and learning were moved online nation-wide. The convenient sampling technique was used, for data collection from Chinese university students. There were a total of 615 students that participated in the survey and data gathered in five months from November 2021 till March 2022. Covariance-based structural equation modelling (CB-SEM) in SPSS V.25 and AMOS V.22 was used to assess model fitness and hypotheses, as well as construct reliability and validity of the measurement model. The results revealed that FLCA is positively and significantly influence students’ academic success. Furthermore, EIC as a mediator significantly and positively mediate the relationship between FLCA and academic success. The current study shows that emotional intelligence has the ability to reduce students' foreign language anxiety and so improve their language skills. Lastly, classroom environment positively and significantly moderate the relationship between FLCA and emotional intelligence communication.